Does endometrial injury enhances implantation in recurrent in-vitro fertilization failures? A prospective randomized control study from tertiary care center - Neeta Singh; Varnit Toshyan; Sunesh Kumar; Perumal Vanamail; Malti Madhu (Wolters Kluwer Medknow Publications, 2015)
Background: Though Assisted Reproductive Techniques have overcome many fertility disorders, implantation is still considered, the rate-limiting step for the success of IVF. Aim0 : The aim of this study was to evaluate the role of endometrial scratching in improving the implantation rate in patients undergoing IVF-ET cycles. Design: Prospective randomized control trial. Methods and Material: Sixty infertile women with a history of >1 previous failed IVF-ET cycles were randomizedinto two groups of 30 each. The patients in group 1 underwent endometrial scratching once between days 14-21 of menstrual cycle in the cycle prior to embryo transfer (ET), while in group 2scratching were not done. Implantation rate, ongoing pregnancy rate, abortion rate and live birth rate were comparedbetween both groups. Statistical Analysis: Mean values were compared between two groups using Student's't' independent test. Frequency distributions of categorical variables were compared using Chi-Square/ Fisher's exact test as appropriate. Results: Implantation rate in group 1 was 19.4% whereas in group 2 it was 8.1%. Difference between two groups was statistically significant (P =0.028). The live birth rate was higher in the group 2 compared to group 1, however this difference was not statistically significant (3.3% vs 10%, P =0.612). No significant difference was observed between the two groups regarding the ongoing pregnancy rate (16.7% vs 0.0%; P =0.052), abortion rate (10.0% vs 3.3%, P =0.612) and miscarriage rate (6.7% vs 3.3%, P =0.99). Conclusions: Implantation rate increases significantly after endometrial scratching in patients with previous failed IVF-ET.